THE INFLUENCE OF QRIS USAGE ON FINANCIAL RECORDING ACCOUNTABILITY WITH FINANCIAL LITERACY AS A MEDIATION VARIABLE: EVIDENCE FROM MSMES IN DENPASAR, INDONESIA - Kadek Dinda Juliamita Kesuma; Putu Putri Prawitasari (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2026)
This study aims to analyze the effect of QRIS (Quick Response Code Indonesian Standard) usage on financial recording accountability with financial literacy as a mediating variable. Based on the Technology Acceptance Model (TAM), this research employs a quantitative approach using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Data were collected through questionnaires from 100 MSMEs in Denpasar, selected through purposive sampling. The results indicate that QRIS usage has a positive and significant direct effect on financial recording accountability. Furthermore, QRIS usage positively influences financial literacy, which in turn enhances financial recording accountability. Financial literacy also partially mediates the relationship between QRIS usage and financial recording accountability. These findings confirm that the adoption of digital payment technology can improve financial accountability, especially when supported by adequate financial literacy. The study contributes to the extension of TAM in the context of digital financial accountability and provides practical insights for policymakers, financial institutions, and MSMEs in enhancing digital financial governance.